Geomechnaics applications in underground hardrock mining - Pariseau, W.G (Society of Mining Engineers of the Ameriacan Institute of Mining, Metallurgical, and Petroleum Engineers (AIME),Inc.PE, Inc., 1984)
Papers of a symposium (presumably) organized by the Geomechanics Unit Committee of the Society of Mining Engineers of AIME.